A Prospective Observational Study On Clinical Profile And Immediate Outcome Of Children Requiring HFNC Oxygen Therapy In A Tertiary Care Hospital - Sai Rakshak, Balay; T Nair, Bindu; Vij, Amit; Kumar Thapar, Rajeev; Amraik, Sukriti (Journal of Neonatal Surgery, 2025)
Objective: To evaluate the clinical profile and immediate outcomes of pediatric patients receiving high-flow nasal cannula (HFNC) oxygen therapy for respiratory distress. Design: Prospective observational study. Methods: Eighty children (0 months to 18 years) admitted to the PICU/NICU of a tertiary care hospital with acute respiratory distress and hypoxia were included. Patients whose parents did not provide consent or those with facial deformities preventing HFNC application were excluded. Improvements in respiratory distress, oxygenation, the need for escalation to other ventilation methods (CPAP/mechanical ventilation), duration of HFNC therapy, and the length of hospital stay were measured. Results: The study included 80 patients: 21.25% neonates, 27.5% infants, 30% children aged 1-5 years, and 21.25% children >5 years; 66.25% were male. Common respiratory distress signs included chest retractions (83.75%), nasal flaring (73.75%), and head bobbing (38.75%). The mean SpO2 was 92.62% (range: 72-99), the mean heart rate was 128.51 bpm (range: 77-207), and the mean respiratory rate was 50.42 breaths/min (range: 20-82). The most common indications for HFNC were respiratory distress of varied etiology (41.25%) and pneumonia (37.5%). Mean initial HFNC settings were FiO2 42% and flow 18.58 L/min, while weaning FiO2 27.43% and flow 9.64 L/min. The mean HFNC duration was 43.5 hours, and the mean hospital stay was 10 days. 83.75% of patients recovered with HFNC, 10% required invasive ventilation, and 6.25% required non-invasive ventilation. No interface-related issues were observed. Conclusions: HFNC therapy is an effective intervention for managing pediatric respiratory distress, significantly improving oxygenation and reducing the need for invasive ventilation.